Lymphoid structures of the waders’ (Charadrii) digestive tract - Харченко, Л. П.; Ликова, І. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Digestive tract lymphoid structures of 12 species of waders (Charadrii) have been investigated and described for the first time. It has been found out that protective structures of the digestive tube wall are lymphoid nodules and lymphocytes diffusely located in the lamina propria, in the muscle and serosa. Lymphoid nodules in all parts of the digestive tract are not encapsulated. In the species of waders studied presence of Meckel’s diverticulum, which can be considered as a peripheral organ of the immune system has been noticed. It has been found out that the largest amount of lymphoid tissue is concentrated in the anterior part of the digestive tube (esophagus) and in the posterior part (rectum).